Saturn and Jupiter Revisited - Wetters, Brent (Nordlit, 2020)
I composed Saturn and Jupiter as part of my Master’s degree thesis at Wesleyan University in 2003. It is an electro-acoustic and soundscape composition that responds to Glenn Gould’s 1967 radio documentary, The Idea of North. I made the source recordings while on a week-long trip to Churchill, Manitoba, where I took the same train that Gould had taken some thirty years earlier. Saturn and Jupiter responds both to the ideas in Gould’s documentary in the form of interviews, and compositionally by imposing considerably more atmospheric space into the work. Where Gould’s documentary is noisy with talking – Gould famously pioneered a technique he called ‘contrapuntal radio’ where he layers multiple speaking voices simultaneously – the spoken components of my documentary are quite sparse. This new presentation commemorates the re-opening of the Winnipeg – Churchill train line after suffering massive flooding damage in 2017. In this version, listeners are invited to hear and view to the 32 movements in a customizable configuration. The interactive map allows users to select the movements, which are each named for a stop on the train line, and have them compiled into a playlist.